Utilization of waste rubber fiber considering modification in strength reduction factor and its effect on the behavior of concrete. (2020) - Srivastava, Shubham; Kumar Rao, Alok; Zain, Mohd.; Kumar, Rajesh
Abstract: In this Study, the improvisation on mix design and the analysis of the strength of rubberized concrete is carried out. The carbon fiber is cut in the prescribed ratio and used for the partial replacement of coarse aggregates. The carbon fibers were mixed with the concrete to form a Rubberized concrete. To obtain a rubberized concrete mixture, all mix design parameters were kept constant as given by the IS-456 method except for the coarse aggregate constituents. The coarse aggregate of the concrete was replaced by 5%, 10%, 15%, 20% and 25% of its weight. The fine aggregate was sieved using 2.36 mm in order to pass through the holes of the carbon fiber to make a strong contact with the cement matrix. From some experimental results of compressive strength testing it was observed that both plain and rubberized concrete developing similar strength over the curing period as expected. For all concrete mixtures, the rate of compressive strength developed was high between 7 and 14 days and slow between 14 and 28 days. Also, it was noted that irrespective of the curing period, there was a systematic reduction in compressive strength with increasing rubber content of the composite. Some experimental investigations observed that a high percentage of carbon fiber mixed cylinders took a longer time to crackdown because of the elastic nature of the fibers when bearing the loading. Moreover, it was observed that the above said rubberized concrete did not exhibit brittle failure under compression or split tension.